Banana Wars and the Multiplicity of Conflicts in Commodity Chains - Kees Jansen (European Review of Latin American and Caribbean Studies, 2006)
– In the Shadows of State and Capital: The United Fruit Company, Popular Struggle, and Agrarian Restructuring in Ecuador, 1900-1995, by S. Striffler. Durham & London: Duke University Press, 2002. – Banana Wars: Power, Production, and History in the Americas, edited by S. Striffler and M. Moberg. Durham: Duke U.P., 2003. – Banana Wars: The Anatomy of a Trade Dispute, edited by T.E. Josling and T.G. Taylor. Oxon: CABI Publishing, 2003. – Smart Alliance: How a Global Corporation and Environmental Activists Transformed a Tarnished Brand, by J.G. Taylor and P.J. Scharlin. New Haven: Yale University Press, 2004. – Banana Wars: The Price of Free Trade: A Caribbean Perspective, by G. Myers. London: Zed, 2004. – The Banana Wars: United States Intervention in the Caribbean, 1898-1934, by L.D. Langley. Wilmington: Scholarly Resources Inc. Revised 2002, first published in 1983.